1984
DOI: 10.1029/gl011i001p00080
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of 10m resolution scalar velocity profiles in the stratosphere

Abstract: Vertical profiles of scalar horizontal winds have been measured at high resolution (10m) in the 13 to 37 km region of the stratosphere. This resolution (at that range of altitude) represents the state‐of‐the‐art, and is unique. Our goal was to ascertain whether or not the internal waves of the stratosphere behave consistently with the Garrett‐Munk model which was originally created for oceanic internal waves. The power spectral densities (PSD's) of five profiles are presented and it is found that (a) they clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 10 publications
0
63
0
Order By: Relevance
“…Here the term "universal" refers to the spectral structure of wind and temperature fluctuations, especially the spectral slope in the high wavenumber region, and is nearly independent of height, season, and geographical location. Decades of observations by different ground-based and satellite-borne instruments (Dewan et al, 1984;Dewan and Good, 1986;Smith et al, 1987;Fritts and Chou, 1987;Fritts et al, 1988;Tsuda et al, 1989;Wilson et al, 1990;Senft et al, 1993;Eckermann, 1999) further confirmed the universality. These observations revealed that in the large wavenumber region, i.e., the spectral tail region, the spectrum has a nearly universal index of −3.…”
Section: Introductionmentioning
confidence: 56%
“…Here the term "universal" refers to the spectral structure of wind and temperature fluctuations, especially the spectral slope in the high wavenumber region, and is nearly independent of height, season, and geographical location. Decades of observations by different ground-based and satellite-borne instruments (Dewan et al, 1984;Dewan and Good, 1986;Smith et al, 1987;Fritts and Chou, 1987;Fritts et al, 1988;Tsuda et al, 1989;Wilson et al, 1990;Senft et al, 1993;Eckermann, 1999) further confirmed the universality. These observations revealed that in the large wavenumber region, i.e., the spectral tail region, the spectrum has a nearly universal index of −3.…”
Section: Introductionmentioning
confidence: 56%
“…In recent years, the Rayleigh lidar technique has emerged as an effective means to study the gravity wave activity in the middle atmosphere over the height range of 30-70 km Hauchecorne, 1981, 1991;Wilson et al, 1990a, b;Gardner et al, 1989;Whiteway and Carswell, 1995;McDonald et al, 1998;Sivakumar et al, 2006;Ramkumar et al, 2006;Antonita et al, 2007). Further techniques provided important results, including rocketsonde measurements (Dewan et al, 1984), balloon soundings (Fritts et al, 1988;Nastrom et al, 1997). Radiosonde measurements, supplying wind velocity and temperature data in the troposphere and lower stratosphere, provided important information on wave climatology, sources, and effects in the lower atmosphere (Allen and Vincent, 1995;Vincent et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the radar provides the information on both frequency and vertical wave number spectra, much of the current theoretical focus is on understanding the nature of the vertical wave number spectrum of gravity waves. A key finding of many experimental studies on wave number and frequency power spectra of atmospheric gravity wave motions was that their spectral characteristics are widely uniform in frequency and wave number, despite different generation sources, meteorological conditions, and locations of observations (VanZandt, 1982;Dewan et al, 1984;Tsuda et al, 1989). A number of different theories have been developed to explain these observations and thus predict essentially the same vertical wave number spectrum, independent of the varying background conditions (Dewan and Good, 1986;Smith et al, 1987;Weinstock, 1990;Hines, 1991;Zhu, 1994;Gardner, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, VanZandt [1982] and other observational studies [e.g., Dewan et al, 1984;Smith et al, 1987] suggested that the vertical wavenumber spectrum of horizontal wind fluctuations displayed a universal small-scale "tail" with a log-log slope between about -2.5 and -3 and an amplitude that is nearly independent of height. A number of competing theories have been proposed to explain the universal character of the spectra and the small-scale "saturated" tail in particular.…”
Section: Introductionmentioning
confidence: 99%